2014
DOI: 10.1155/2014/584986
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Opioid Misuse in Italian Patients with Chronic Noncancer Pain

Abstract: Objective. Opioid therapy in patients with chronic noncancer pain must be preceded by evaluation of the risk of opioid misuse. The aim of this study was to evaluate the predictive validity of the Italian translation of the Pain Medication Questionnaire (PMQ) and of the Diagnosis Intractability Risk and Efficacy Score (DIRE) in chronic pain patients. Design. 75 chronic noncancer pain patients treated with opioids were enrolled and followed longitudinally. Risk of opioid misuse was evaluated through PMQ, DIRE, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…9pt?>Some clinical symptoms related to the adverse effects of opioids, such as constipation and nausea, were similar to those found by [46]. Similarly, the unpredictable recurring vaso-occlusive crises experienced by sickle cell patients were associated with pain in various parts of the body, leading to hospitalization and low quality of life, as observed in other studies [18, 47, 48]. Moreover, insomnia in some patients was related to opioid abuse, probably due to the recurrence of chronic pain in this population [49, 50].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…9pt?>Some clinical symptoms related to the adverse effects of opioids, such as constipation and nausea, were similar to those found by [46]. Similarly, the unpredictable recurring vaso-occlusive crises experienced by sickle cell patients were associated with pain in various parts of the body, leading to hospitalization and low quality of life, as observed in other studies [18, 47, 48]. Moreover, insomnia in some patients was related to opioid abuse, probably due to the recurrence of chronic pain in this population [49, 50].…”
Section: Discussionsupporting
confidence: 80%
“…The original Pain Medication Questionnaire (PMQ) was developed for this study and validated in the USA by (Additional file 1) to assess the risk of opioid abuse in patients with chronic non-oncological pain in a series of four studies [1417]. However, it was only adapted for Italian [18], and is being submitted to the entire cross-cultural adaptation process in this study, as well as clinical validation in a subsequent investigation, both carried out by the research team. As such, the aims of the present study were to transculturally-adapt and check the content and face validity of the PMQ for use in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies [57][58][59] were found which compared different tools, as shown in Table 5. The DIRE (diagnosis intractability risk and efficacy) score, included here, was excluded from this review as it was retrospective.…”
Section: Studies Comparing Different Toolsmentioning
confidence: 99%
“…Opioid analgesics are the mainstay for pharmacological treatment of chronic moderate-to-severe pain, with their propensity to improve the quality of life. Although there is an agreement on their use in acute and cancer pain, long-term use for CNCP remains controversial [2][3][4][5]. Side effects, absence of any improvement in physical function, misuse, abuse, and addiction are relatively common during chronic opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines recommend that the use of opioids in patients with CNCP must be preceded by an assessment of potential benefits and risks of aberrant drug-related behaviors and should include a psychological and psychiatric assessment [2,10]. Different kinds of tools have been developed for this purpose in recent years [11,12]; Pain Medication Questionnaire [13] and Diagnosis Intractability Risk and Efficacy (DIRE) score [14] were created specifically for chronic pain patients.…”
Section: Introductionmentioning
confidence: 99%